Le présent altéré - Serrano, Gemma (ETHICS IN PROGRESS, 2017)
Our working hypothesis is that the digital culture is remodeling a temporal affect of existence. We attempt to describe how our experience of present time is altered by the increase of digital memory, together with the progressive disappearance of « memory recall » and expectation. This altered presence opens up loopholes which could be called dreams, desire, promise, latency or God. Thus anticipatory algorithm and data translation of present actions of the subject are not a definitive tragedy of our time.